MEDIA TEKNOLOGI UNTUK MEMOTIVASI DAN PRESTASI MAHASISWA - Disa Devia; Fadhillah Khairunnisa; Gusmaneli Gusmaneli (CV. ADIBA AISHA AMIRA, 2024)
Nowadays, with the rapid development of technology and information such as online media and the internet, everything can now be accessed through gadgets, including information that supports student learning activities. Even now with the development of technology, gadget users can now access a variety of information. Online media itself was born in 1990 because of the advantages of internet media. There are several factors that improve student learning achievement, not only gadget competition, but there is one important factor, namely the motivation factor. Psychological factors play a very important role for students where this motivation plays a role. Because of its important role in learning, namely as a motivator or stimulant for the soul of the person who carries out learning activities, learning motivation is one of the factors that exist in a person who motivates a person to carry out a learning activity. a motivator. Doing something optimally to achieve the maximum results you want to achieve.